Study on Mechanical Properties and Application of Magnesium Phosphate Modified Cement - Chen, Shihao (Transactions on Engineering and Technology Research, 2024)
In today's environment, the use of magnesium phosphate cement is more and more extensive, but it still faces problems such as fast setting and brittleness. This paper aims to solve the problem and improve the fire resistance of magnesium phosphate cement by modifying the compound. Through literature search, it is found that the incorporation of vinyl acetate ethylene copolymer emulsion (VAE) and anionic polyacrylamide (APAM) into cement can improve the problem of fast setting time and improve the flexibility of modified magnesium phosphate cement. The glass fiber can increase the bending and compressive strength of magnesium phosphate cement by adding silane coupling agent into cement. The fire resistance of phosphate cement can be greatly improved by using expanded perlite as fire retardant coating. The main research significance of this paper is to solve the shortcomings of magnesium phosphate cement and make the use of magnesium phosphate cement more extensive and safer.